2020
DOI: 10.31234/osf.io/bszm4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Corrections of Political Misinformation: No Evidence for an Effect of Partisan Worldview in a U.S. Convenience Sample

Abstract: Misinformation often has a continuing effect on people’s reasoning despite clear correction. One factor assumed to affect post-correction reliance on misinformation is worldview-driven motivated reasoning. For example, a recent study with an Australian undergraduate sample found that when politically-situated misinformation was retracted, political partisanship influenced the effectiveness of the retraction. This worldview effect was asymmetrical, that is, particularly pronounced in politically-conservative pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Results typically show that a direct retraction significantly reduces reliance on the critical information relative to the no-retraction control condition, but does not eliminate the influence down to the no-misinformation baseline (e.g., E c k e r , H o g a n , & L e w a n d o w s k y , 2 0 1 7 ; Ecker, Lewandowsky, & Apai, 2011). Continued influence has also been demonstrated with real-world news (Lewandowsky, Stritzke, Oberauer, & Morales, 2005), common myths (Ferrero, Hardwicke, Konstantinidis, & Vadillo, 2020;Sinclair, Stanley, & Seli, 2019;Swire, Ecker, & Lewandowsky, 2017), political misconceptions (Ecker & Ang, 2019; also see Ecker, Sze, & Andreotta, 2021;Nyhan & Reifler, 2010;Wood & Porter, 2019), with subtle and implicit misinformation (Ecker, Lewandowsky, Chang, & Pillai, 2014;Rich & Zaragoza, 2016), false allegations (Thorson, 2016; but see Ecker & Rodricks, 2020), and when the misinformation is presented initially as a negation that is later reinstated .…”
Section: Introductionmentioning
confidence: 99%
“…Results typically show that a direct retraction significantly reduces reliance on the critical information relative to the no-retraction control condition, but does not eliminate the influence down to the no-misinformation baseline (e.g., E c k e r , H o g a n , & L e w a n d o w s k y , 2 0 1 7 ; Ecker, Lewandowsky, & Apai, 2011). Continued influence has also been demonstrated with real-world news (Lewandowsky, Stritzke, Oberauer, & Morales, 2005), common myths (Ferrero, Hardwicke, Konstantinidis, & Vadillo, 2020;Sinclair, Stanley, & Seli, 2019;Swire, Ecker, & Lewandowsky, 2017), political misconceptions (Ecker & Ang, 2019; also see Ecker, Sze, & Andreotta, 2021;Nyhan & Reifler, 2010;Wood & Porter, 2019), with subtle and implicit misinformation (Ecker, Lewandowsky, Chang, & Pillai, 2014;Rich & Zaragoza, 2016), false allegations (Thorson, 2016; but see Ecker & Rodricks, 2020), and when the misinformation is presented initially as a negation that is later reinstated .…”
Section: Introductionmentioning
confidence: 99%
“…Using both perspectives, researchers have been able to uncover several aspects related to the mechanisms underlying the CIE. For example, it has been shown that memory-related processes at both encoding (e.g., Ecker, Lewandowsky, Swire, et al, 2011) and retrieval (e.g., Swire, Ecker, & Lewandowsky, 2017) can contribute to the CIE. Furthermore, cognitive biases have been shown to influence the CIE through perceived source credibility (e.g., Ecker & Antonio, 2020; Guillory & Geraci, 2013), and political beliefs (e.g., Ecker & Ang, 2019; Lewandowsky et al, 2005; Nyhan & Reifler, 2010; but see Ecker et al, 2021; Swire-Thompson, DeGutis, & Lazer, 2020; Swire-Thompson, Ecker, et al, 2020; Wood & Porter, 2019). However, experiments in both lines of investigation have predominantly manipulated aspects of information presentation to observe their impact on the CIE. For example, studies have manipulated study-test delays and the number of misinformation/retraction repetitions (Ecker et al, 2011; Swire, Ecker, & Lewandowsky, 2017), the explicitness of the misinformation (Rich & Zaragoza, 2016), its emotional valence (Chang et al, 2019; Ecker, Lewandowsky, & Apai, 2011; Trevors & Kendeou, 2020), whether participants were warned about the CIE prior to misinformation presentation (Clayton et al, 2019; Ecker et al, 2010), or the trustworthiness of the source (e.g., Ecker & Antonio, 2020; Guillory & Geraci, 2013; Swire-Thompson, Ecker, et al, 2020).…”
mentioning
confidence: 99%